Biodiversidad y distribución de la ictiofauna mesopotámica - López, Hugo Luis (2005)
We analyze the fish fauna of the Mesopotamian Region in northeastern Argentina, providing detailed lists of species, and indicating endemics and exotic ones. This region, with a large number of aquatic environments, has the largest ichthyological richness of Argentina. Fishes, mostly of Brazilian origin, are distributed in 12 orders, 42 families, 162 genera and 341 species, of which 36 are endemic. Limit of distribution of some orders, families and species are pointed out. A comparative analysis is made of the fish fauna occurring in the Iguazú, Uruguay and Paraná rivers and in the Entre Rios Delta region. Areas of outstanding diversity, as well as those protected at national level are discussed. Ramsar sites and other wetlands are considered and anthropic impacts are indicated.